2014
DOI: 10.1038/ncomms6182
|View full text |Cite
|
Sign up to set email alerts
|

Parkin regulates kainate receptors by interacting with the GluK2 subunit

Abstract: Although loss-of-function mutations in the PARK2 gene, the gene that encodes the protein parkin, cause autosomal recessive juvenile parkinsonism, the responsible molecular mechanisms remain unclear. Evidence suggests that a loss of parkin dysregulates excitatory synapses. Here we show that parkin interacts with the kainate receptor (KAR) GluK2 subunit and regulates KAR function. Loss of parkin function in primary cultured neurons causes GluK2 protein to accumulate in the plasma membrane, potentiates KAR curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 40 publications
5
42
0
Order By: Relevance
“…Parkin ubiquitinates GluK2 in both heterologous cells and cultured neurons, and knockdown of Parkin increased GluK2 surface expression and increased vulnerability of hippocampal neurons to kainate-induced excitotoxicity. Furthermore, in a mouse model of autosomal recessive juvenile Parkinson's expressing a truncated form of Parkin, there are increased levels of GluK2 in substantia nigra and corresponding increases in cortex samples from human patients expressing mutations in Parkin [105]. Thus, GluK2 is a Parkin target that may contribute to the excitotoxic cell death of substantia nigra neurons in Parkinson's disease.…”
Section: Ubiquitinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Parkin ubiquitinates GluK2 in both heterologous cells and cultured neurons, and knockdown of Parkin increased GluK2 surface expression and increased vulnerability of hippocampal neurons to kainate-induced excitotoxicity. Furthermore, in a mouse model of autosomal recessive juvenile Parkinson's expressing a truncated form of Parkin, there are increased levels of GluK2 in substantia nigra and corresponding increases in cortex samples from human patients expressing mutations in Parkin [105]. Thus, GluK2 is a Parkin target that may contribute to the excitotoxic cell death of substantia nigra neurons in Parkinson's disease.…”
Section: Ubiquitinationmentioning
confidence: 99%
“…A recent study identified that the Parkinson's diseaseassociated ubiquitin ligase Parkin directly interacts with and ubiquitinates the C-terminus of GluK2 [105]. Parkin ubiquitinates GluK2 in both heterologous cells and cultured neurons, and knockdown of Parkin increased GluK2 surface expression and increased vulnerability of hippocampal neurons to kainate-induced excitotoxicity.…”
Section: Ubiquitinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, defects in glutamatergic transmission and plasticity are reported at hippocampal and corticostriatal synapses deficient in Parkin (15)(16)(17)(18)(19)(20). Parkin's mechanisms of action at excitatory synapses remain poorly understood, although its ubiquitinating activity has been found to regulate the stability and function of multiple synaptic substrates, including the presynaptic vesicle-associated protein synaptotagmins XI and IV, the postsynaptic scaffold PICK1, and the kainate receptor subunit GluK2 (21)(22)(23)(24)(25)(26). Furthermore, our recent work demonstrates that Parkin also has a structural role at the synapse, linking postsynaptic endocytic zones required for AMPA-type glutamate receptor (AMPAR) capture and internalization to the postsynaptic density through a direct interaction with the scaffold protein Homer1 (19).…”
Section: Introductionmentioning
confidence: 99%
“…Parkin overexpression reverses A尾-induced changes in the mitochondrial TCA cycle and restores amino acid and neurotransmitter levels in AD models [68,124,129]. More recent data indicate thatexpression of a PD-linked Parkin mutant in the mouse brain causes glutamate excitotoxicity via regulation of kainate receptors [130]. High-frequency 1 H/ 13 C NMR spectroscopy shows that brain 13 C concentration is significantly increased in glutamate C4 (fig.…”
Section: Parkin and Amino Acid Balancementioning
confidence: 99%